Adrenocortical oncocytic neoplasms: a case report - Cao, Lintao; Dong, Xiaoxiao; Tan, Jiufeng; Wang, Zhenpu (Frontiers in Medicine, 2025)
Adrenocortical oncocytic neoplasms (ACONs) are very rare in adrenal cortical tumors. One case was reported in this paper. During the physical examination, a soft tissue density shadow was about 6 cm × 5.7 cm in the right adrenal gland. A preoperative diagnosis was adrenal pheochromocytoma with concurrent laparoscopic resection of the right adrenal tumor. Postoperative pathological results rewarded the adrenal cortical oncocytic neoplasms ACONs. After 11-months of postoperative follow-up, the patient had no signs of tumor recurrence and related complications.